The economic impacts of house screening against malaria transmission: Experimental evidence from eastern Zambia. (March 2023) - Chisanga, Brian; Bulte, Erwin; Kassie, Menale; Mutero, Clifford; Masaninga, Freddie; Sangoro, Onyango Peter
Abstract: Malaria imposes an economic burden for human populations in many African countries, and this burden may be reduced through house screening initiatives. We use a randomized controlled trial to measure the economic impacts of house screening against malaria infection. We use a sample of 800 households from 89 villages in rural and peri-urban Zambia to collect baseline data in August 2019 and endline data in August 2020. The main outcome variables are (self-reported) malaria prevalence rates, labor supply, and income, and consider individual and household-level outcomes. House screening reduces malaria prevalence, the number of sick days due to malaria, and the number of malaria episodes. Impacts on adults are more pronounced than on children. In terms of economic impacts, house screening increases labor supply and (household) income. We find particularly large effects on labor supply for women household members. A cost-benefit analysis, based on estimated benefits and measured costs, suggests that the private benefits of house screening exceed the costs. While not all houses are suitable for house screening, we conclude that screening is a promising and cost-effective approach to reduce malaria infections. Highlights: We organize an experiment to evaluate the socio-economic impacts of house screening in Zambia. House screening reduces the prevalence of malaria. House screening increases household labor supply and raises household income. The discounted income gains of house screening exceed the costs. The impact of house screening are heterogeneous across gender and age groups.